Water vapour effects of cyclic oxidation on Fe-Cr alloys - N.K. Othman,; N.Othman,; J. Zhang,; D.J. Young, (Universiti Kebangsaan Malaysia, 2010)
Fe-Cr alloys (Cr: 9-30 wt%) were subjected to cyclic oxidation in Ar-20%O2, Ar-20%O2-5%H2O and Ar-10%H2-5%H2O (partial pressure of oxygen, pO2 = 1.1 ¥ 10-16atm). Oxidation weight change measurement showed that in general, increasing Cr content reduced the oxidation rate. At Cr < 17%Cr, breakaway oxidation was observed. However, for Cr > 25%, the weight gain became very low due to formation of Cr2O3 layer. Adding 5%H2O to Ar-20%O2 accelerated the oxidation rate of alloys with Cr < 20%. However, this accelerating effect did not appear in high chromium content alloys. XRD analysis showed that for alloys with Cr < 20%, wustite and spinel were formed at low pO2, while at high pO2, hematite, iron oxide and spinel were formed. For high Cr content alloy only Cr2O3 was detected. Cross-section analysis showed that the spinel was formed by internal oxidation. The thickness and size of this internal oxide zone increased with increasing Cr content. A dense chromia layer was observed when the Cr content was above 25%. The oxides scales formed in water vapour were more porous and less compact than the scale formed in dry oxygen. The accelerating effect of water vapour on Fe-Cr oxidation is discussed in terms of gas-solid interactions.